Model with two periods of inflation - Schettler, Simon; Schaffner-Bielich, Jürgen (Physical review, 2016)
A scenario with two subsequent periods of inflationary expansion in the very early Universe is examined. The model is based on a potential motivated by symmetries being found in field theory at high energy. For various parameter sets of the potential, the spectra of scalar and tensor perturbations that are expected to originate from this scenario are calculated. Also the beginning of the reheating epoch connecting the second inflation with thermal equilibrium is studied.
Gesehen am 13.05.2020